Catching Up to the Technological Frontier? : Understanding Firm-level Innovation and Productivity in Kenya - Cirera, Xavier (World Bank Group, Washington, DC, 2015)
Kenya s economy has undergone a significant process of structural transformation over the last decade. Since 2002, the economy has shown an accelerating trend with GDP growth increasing steadily from below 1 percent in 2002 to 7 percent in 2007. After a slowdown in GDP growth to 1.5 percent and 2.7 percent in 2008 and 2009 respectively, economic growth started to rebound in 2010. Amidst this positive growth context, in October 2013, the Kenyan Government launched the Second Medium-Term Plan (MTP-2) of the Vision 2030. The aim of Kenya s Vision 2030 is to create a globally competitive and prosperous country with a high quality of life by 2030 and to shift the country s status to upper-middle income level.